Pelatihan Penyusunan dan Submission Artikel Jurnal ELITE Bagi Mahasiswa Tingkat Akhir Program Studi Sastra Inggris Fib Uho - Nuru, Sarniati; Masri, Fina Amalia; Gultom, Eva Solina; Rahmawati; Nurjannah; Sofyan, Nur Israfyan; Arman (LP2M IAIN Sultan Amai Gorontalo, 2024)
Abstract: Writing a scientific journal is not only carried out by teachers, lecturers, or researchers, but is also carried out by students, especially the final-year students in preparing to write scientific journal as prerequisite for their graduation. The aim of this training programme is to hone students’ writing skill in creating clear, structures, and scientific journal reports. Apart from the writing aspect, it is hoped that scientific journals resulting from students’ research can be published. As a result, it can broaden their horizons regarding their knowledge in certain research field. Apart from honing writing skill, writing scientific journals also aims to train researchers to think critically, objectively, and systematically to understand problems in more depth and think ahead. Writing a scientific journal and then publishing it will become a good track record that shows someone’s competence and can be a good portfolio, especially when planning further studies or to obtain a scholarship. Keywords: Article; Elite Journal; English Literature; and submission.